Land Grant and Plat, Camden County, 1886 - State of Georgia, Camden County (Valdosta, GA: Valdosta State University Archives and Special Collections, 2020, 1886)
Land Grant and Plat, Camden County, 1886. Handwritten record on printed form with ribbon and seal. Plat and land grant to E.J. Stafford by Governor John B. Gordon for two hundred acres in Camden County, Georgia. December 9, 1886. 3 pages.
1 electronic document [PDF/A]. Includes TIFF and JP2 images. Digitized by the Digital Library of Georgia, September 2019.
Keywords: Deeds; Camden County (Ga.); Court Records; Records and correspondence; Cadastral maps; Gordon, John Brown, 1832-1904; Surveying